Psychological Factors In Developing Students’Creative Thinking - Gazibekova Gulavza Ergashevna (Euro Asian Journal Publishing, 2025)
The article explores the psychological factors that contribute to the development of creative thinking among students in the educational process. Creative thinking is defined as the ability to generate original ideas, find alternative solutions, and approach problems in innovative ways. The study emphasizes that creative thinking development depends on various internal and external psychological factors, including motivation, cognitive flexibility, emotional intelligence, self-esteem, and the learning environment. The author highlights that teachers play a crucial role in creating a psychologically supportive and stimulating classroom atmosphere where students feel free to express their ideas without fear of judgment. The research also analyzes how personal traits such as curiosity, openness to experience, and intrinsic motivation shape the creative process. Furthermore, the paper discusses methods of psychological stimulation—such as brainstorming, problem-based learning, and reflective exercises—that enhance students’ ability to think independently and creatively. Overall, the study concludes that fostering creative thinking requires an integrative psychological approach combining emotional, cognitive, and motivational components within the educational framework.
Keywords: psychological factors; Creative thinking; motivation